Influence of Materialism, Financial Literacy, and Risk Perception on Propensity to Indebtedness Among Peer-to-Peer Lending Users: A Case Study of Generation Z in Tangerang City - Andi Yuswandi; Hamdani Hamdani (Eduvest - Journal of Universal Studies, 2025)
Advances in financial technology, particularly peer-to-peer (P2P) lending, have facilitated easier access to credit for Generation Z. However, this convenience also increases the potential for excessive indebtedness. This study aims to analyze the influence of materialism, financial literacy, and risk perception on the propensity to indebtedness of P2P lending users in Tangerang City. A quantitative approach was employed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with Smart PLS 4. Data were collected from 152 Generation Z respondents who actively used P2P lending services. The analysis results indicate that materialism has a positive and significant effect on the propensity to indebtedness, whereas financial literacy has a negative and significant effect, suggesting that higher financial literacy can reduce the tendency to accumulate debt. Additionally, risk perception significantly influences the propensity to indebtedness, and individuals with lower risk perceptions are more vulnerable to debt. These findings provide insights for regulators and P2P lending service providers when designing financial education strategies and risk mitigation policies to prevent unhealthy borrowing behavior among Generation Z.